Whole genome sequencing of Herpes Simplex Virus 1 directly from human cerebrospinal fluid reveals selective constraints in neurotropic viruses. Issue 1 (20th February 2020) - Lassalle, Florent; Beale, Mathew A; Bharucha, Tehmina; Williams, Charlotte A; Williams, Rachel J; Cudini, Juliana; Goldstein, Richard; Haque, Tanzina; Depledge, Daniel P; Breuer, Judith
Abstract: Herpes Simplex Virus type 1 (HSV-1) chronically infects over 70 per cent of the global population. Clinical manifestations are largely restricted to recurrent epidermal vesicles. However, HSV-1 also leads to encephalitis, the infection of the brain parenchyma, with high associated rates of mortality and morbidity. In this study, we performed target enrichment followed by direct sequencing of HSV-1 genomes, using target enrichment methods on the cerebrospinal fluid (CSF) of clinical encephalitis patients and from skin swabs of epidermal vesicles on non-encephalopathic patients. Phylogenetic analysis revealed high inter-host diversity and little population structure. In contrast, samples from different lesions in the same patient clustered with similar patterns of allelic variants. Comparison of consensus genome sequences shows HSV-1 has been freely recombining, except for distinct islands of linkage disequilibrium (LD). This suggests functional constraints prevent recombination between certain genes, notably those encoding pairs of interacting proteins. Distinct LD patterns characterised subsets of viruses recovered from CSF and skin lesions, which may reflect different evolutionary constraints in different body compartments. Functions of genes under differential constraint related to immunity or tropism and provide new hypotheses on tissue-specific mechanisms of viral infection and latency.